Symbolic reliability analysis and optimization of ECU networks - Glaß, Michael; Lukasiewycz, Martin; Reimann, Felix; Haubelt, Christian; Teich, Jürgen (Proceedings of Design, Automation and Test in Europe (DATE 2008), 2008)
Increasing reliability at a minimum amount of extra cost is a major challenge in todays ECU network design. Considering reliability as an objective already in early design phases has the potential to avoid expensive modifications in later design phases. Hence, there is a need for an appropriate optimization process and efficient analysis techniques to evaluate the found implementations. In this paper, we will show how symbolic techniques can be used to efficiently analyze and optimize such reliable systems. The contribution of this paper is (1) a symbolic reliability analysis that makes use of a partitioned structure function and (2) a symbolic optimization process based on binary ILP solvers. Our case study from the automotive area will show a significant speed-up using our analysis technique. Moreover, our optimization approach is able to offer implementations with considerably improved reliability at no additional costs as well as implementations with reduced costs without decreasing their reliability. © 2008 EDA